Training programmes for forest protection courses at university level. - Ahmad, Abdul Manap
Training programmes in forest protection are gaining recognition and importance not only in developed,but also in developing countries. More emphsis is now attached to such programmes not only in universities,nut also in research institutes and other vocational institutions. Indeed,the public directly involved in forest activities are gradually being made aware of the insect pests and also to assess the extent of the damage. It is this preoccupation to awaken public awareness on the potential loss of wood and timber products that courses in forest protection are now being included and expanded in university. Such programmes are also being offered at least up to informative stage in vocational schools and institutes.